Vital Life-Threatening Hematoma after Implant Insertion in the Anterior Mandible: A Case Report and Review of the Literature - Eik Schiegnitz; Maximilian Moergel; Wilfried Wagner (Case Reports in Dentistry)
Dental implant insertion is considered a safe and reliable surgical procedure and severe complications are seldom reported. However, we present a case of a 52-year-old patient who attended our Department of Oral and Maxillofacial Surgery, Johannes Gutenberg University Medical Center, Mainz, with spreading hematoma in the floor of the mouth and acute airway obstruction after insertion of a dental implant in the anterior mandible. The hematoma was removed and submentally drained by a silicon drainage. However, the progressive swelling of the tongue and the floor of the mouth necessitated a temporary tracheotomy for three days. The review of the literature summarizes guidelines for prevention and management of this life-threatening complication.